Strategi Pemasaran Mampu Menentukan Loyalitas Karyawan PT Peserta Medical Check Up (MCU) Melalui Variabel Kepercayaan (Journal of Hospital Management, 2019)
People who don't feel sick are not necessarily healthy. The act of preventing or treating a disease before it becomes severe will also be easier and cheaper. This is where the main benefits of doing Medical Check Up (MCU), to detect health problems as early as possible and provide information needed for further treatment. This research aims to analyze the effect of the marketing strategy plan and the brand image of Permata Keluarga Hospital on the loyalty of PT employees participating in medical check-up (MCU) with employee trust as an intervening variable. The design of this research is Explanatory Research (Explanatory Research) with a sample of 220 employees from PT who have done MCU examination at Permata Keluarga Hospital 2x. Marketing strategy and brand image are independent variables. Patient trust is the intervening variable and employee loyalty is the dependent variable. This study uses a questionnaire using a Likert scale. Testing data analysis using SEM-AMOS. The results showed that marketing strategy had a positive and significant effect on brand image. The marketing strategy has a positive and significant effect on loyalty. The marketing strategy has a positive and significant effect on trust. Brand image has no significant effect on loyalty. Brand image has a positive and significant effect on trust, trust has a positive and significant effect on loyalty. And the marketing strategy and brand image of Permata Keluarga Hospital influences loyalty which is mediated by the trust of the employees of PT participants of medical check-up (MCU). Keywords: Employee Loyalty, Marketing Strategy, Brand Image, Patient Trust